Temporal Characteristics of the Oropharyngeal and Nasal Microbiota Structure in Crewmembers Stayed 180 Days in the Controlled Ecological Life Support System - Chen, Yanwu; Xu, Chong; Zhong, Chongfa; Lyu, Zhitang; Liu, Junlian; Chen, Zhanghuang; Dun, Huanhuan; Xin, Bingmu; Xie, Qiong (Frontiers in Microbiology, 2021)
Confined experiments are carried out to simulate the closed environment of space capsule on the ground. The Chinese Controlled Ecological Life Support System (CELSS) is designed including a closed-loop system supporting 4 healthy volunteers surviving for 180 days, and we aim to reveal the temporal characteristics of the oropharyngeal and nasal microbiota structure in crewmembers stayed 180 days in the CELSS, so as to accumulate the information about microbiota balance associated with respiratory health for estimating health risk in future spaceflight. We investigated the distribution of microorganisms and their dynamic characteristics in the nasal cavity and oropharynx of occupants with prolonged confinement. Based on the 16S rDNA v3–v4 regions using Illumina high-throughput sequencing technology, the oropharyngeal and nasal microbiota were monitored at eight time points during confinement. There were significant differences between oropharyngeal and nasal microbiota, and there were also individual differences among the same site of different volunteers. Analysis on the structure of the microbiota showed that, in the phylum taxon, the nasal bacteria mainly belonged to Actinobacteria, Firmicutes, Proteobacteria, Bacteroidetes, etc. In addition to the above phyla, in oropharyngeal bacteria Fusobacterial accounted for a relatively high proportion. In the genus taxon, the nasal and oropharyngeal bacteria were independent. Corynebacterium and Staphylococcus were dominant in nasal cavity, and Corynebacterium, Streptococcus, and Neisseria were dominant in oropharynx. With the extension of the confinement time, the abundance of Staphylococcus in the nasal cavity and Neisseria in the oropharynx increased, and the index Chao fluctuated greatly from 30 to 90 days after the volunteers entered the CELSS. Conclusion: The structure and diversity of the nasal and oropharyngeal microbiota changed in the CELSS, and there was the phenomenon of migration between occupants, suggesting that the microbiota structure and health of the respiratory tract could be affected by living in a closed environment for a long time.